PENGGUNAAN GAS AIR MATA DALAM PENGAMANAN PERTANDINGAN SEPAKBOLA DALAM PERSPEKTIF HUKUM POSITIF DI INDONESIA - Putra, Dery Irawan Aditya; Zeinudin, Moh.; Fithry, Abshoril (Fakultas Hukum Universitas Wiraraja, 2023)
Result observationaling to point out 1. FIFA'S order and also PSSI was clear about sharp weapon purpose and Lachrymator may not be brought in evenless is utilized at deep stadium and also stadium outboard, that thing most decants deep section 19b.